Integrate cultures and beliefs into genealogy software for remote communities in Borneo - Edwin, Mit; Cheah, Wai Shiang; Muhammad Asyraf, Khairuddin (IEEE, 2012)
The biggest challenge to precisely model the remote communities cultures in Borneo is to elicit the reliable documentary sources or historical data, as almost of it is not recorded. This is partly due to the accessibility to education, ICT technologies and the development of infrastructure was a bit late by the remote communities in Borneo. Therefore, the possible source of historical data is through oral tradition, which is have limited trace only to several generations back. In order to preserve their cultures and beliefs, a thorough study on remote communities is required in order to present a precise software architecture that can represent their cultures and beliefs in digital form. This paper will discuss the elicitation process and techniques on remote community cultures which related to marriage process, including preparations, events and beliefs before and during the marriage ceremony. These cultures are integrated into a proposed architecture of genealogy software for remote communities. The proposed genealogy software not only accommodates basic information about individuals, including births, marriages, and deaths but the most important component is the culture behind every event for historical records. The idea of this research is not only to preserve genealogy data, but the cultural of minority ethnic group of remote community in Borneo in a new genealogy software, so that the culture will not be extinct.